2009
DOI: 10.1186/1471-2431-9-74
|View full text |Cite
|
Sign up to set email alerts
|

Development and tracking of central patterns of subcutaneous fat of rural South African youth: Ellisras longitudinal study

Abstract: BackgroundIndividuals grow and accumulate central patterns of body fat into the diseases they will suffer from as older adults. The need to elicit the development and tracking of central patterns of body fat from younger age into adolescent remains to be explored.MethodSkinfolds measurements were done according to the standard procedures in the Ellisras Longitudinal Growth and Health Study. In total, 2,225 children--550 preschool and 1,675 primary school--aged 3-10 years (birth cohorts 1993 to 1986) were enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…We observed that not only BMI, but also some of the examined skinfolds and skinfoldbased body fat percentage showed good tracking, in agreement with previous studies [46][47][48]. The utilization of BMI as an indicator of adiposity is often questioned in the literature, since it simultaneously evaluates both the fat and fat-free mass.…”
Section: Discussionsupporting
confidence: 90%
“…We observed that not only BMI, but also some of the examined skinfolds and skinfoldbased body fat percentage showed good tracking, in agreement with previous studies [46][47][48]. The utilization of BMI as an indicator of adiposity is often questioned in the literature, since it simultaneously evaluates both the fat and fat-free mass.…”
Section: Discussionsupporting
confidence: 90%
“…A espessura da PCT sofre variação de acordo com o sexo e a idade, apresentando um aumento progressivo, especialmente no sexo feminino 18,19 . Uma hipótese que pode ser levantada nesta pesquisa é de que a idade escolar talvez não seja o momento adequado para se comprovar a associação entre o baixo peso ao nascer e o acúmulo corporal de gordura.…”
Section: Discussionunclassified
“…Several studies have shown that compared with body mass index, body fat distribution plays a greater role in the development of obesity‐related complications such as cardiovascular disease and type 2 diabetes . Although previous studies have suggested that central fat mass tracks moderately from mid‐childhood into adulthood, it is not known whether body fat distribution measures in infancy are associated with similar measures in later childhood.…”
mentioning
confidence: 99%